Bioactive fungal metabolites as SIRT2 antagonists: A computational quest for cancer treatment - Md. Habib Ullah Masum; Syed Mohammad Lokman; Kazi Chamonara; Md Shahidur Rahman; Erfanul Haq Chowdhury; Rehana Parvin; Md. Rimon Bhuiyan; Md Nafis Enam; Ahmad Abdullah Mahdeen (PLoS ONE, 2025)
SIRT2, a member of the sirtuin protein family, plays a pivotal role in regulating tumor progression by modulating key metabolic pathways and signaling proteins. The regulatory role of this protein has been documented across a variety of cancers. Emphasizing its role in cancer biology, this study employed computer aided drug design (CADD) approach, including molecular docking, dynamics and pharmacoinformatics, to screen fungal metabolites as potential anticancer agents. Subsequent assessments of pharmacokinetics and toxicity revealed that all tested fungal metabolites possessed oral bioavailability, drug-like characteristics, and favorable ADMET profiles. The metabolites also exhibited no hepatotoxicity, carcinogenicity, or mutagenicity, highlighting their significant therapeutic potential and favorable safety profile. The docking analysis further revealed strong binding affinities of the metabolites with the SIRT2, with the MSID001658 showing the highest score (–10.9 kcal/mol), followed by the MSID000672 (−10.2 kcal/mol). Further molecular dynamics simulation evaluated the structural and dynamic stabilities of the SIRT2 in association with the ligands. Although both complexes showed overall stability, the MSID000672 had larger RMSD variations, whereas the MSID001658 maintained consistent structural integrity throughout the simulation. Furthermore, the binding of MSID000672 was associated with increased solvent exposure, in contrast to the more compact molecular surface area (MolSA) and radius of gyration (Rg) profile observed for the MSID001658. The PCA indicated compact clustering (53.6%) for the SIRT2_MSID000672 complex, whereas the SIRT2_MSID001658 had a larger variance (70.9%) of flexibility. The DCCM further revealed enhanced coordination of internal movements in the SIRT2_MSID000672 complexes. Finally, the MSID001658 fosters a compact, stable complex with the SIRT2, whereas the MSID000672 increases conformational flexibility and solvent accessibility. These results support the notion that the MSID000672 might be an effective anticancer agent if subjected to more experimental trials.